2003
DOI: 10.1373/49.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Validation of the Beckman Coulter Access Analyzer in a Second-Trimester Down Syndrome Serum Screening Application

Abstract: Background: Mid-trimester maternal serum ␣-fetoprotein (AFP) and unconjugated estriol (uE3) are 30% lower and human chorionic gonadotropin (hCG) is twofold higher in Down syndrome pregnancies compared with unaffected pregnancies. In maternal serum screening, patient-specific risks are calculated using published gaussian frequency distribution parameters for these three markers obtained with previously available immunoassays. New immunoassays must generate similar distribution parameters if the accuracy of assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 17 publications
0
33
3
Order By: Relevance
“…When the median values of the serum markers at each gestational age were compared with the published values for Caucasian women (16), the median values of all the serum markers were higher in Korean women than Caucasian women. The range of ratios was highest for inhibin A (range, 1.5-1.9), followed by uE3, AFP, and hCG (Table 2).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When the median values of the serum markers at each gestational age were compared with the published values for Caucasian women (16), the median values of all the serum markers were higher in Korean women than Caucasian women. The range of ratios was highest for inhibin A (range, 1.5-1.9), followed by uE3, AFP, and hCG (Table 2).…”
Section: Resultsmentioning
confidence: 96%
“… * Comparison between unaffected pregnancies and Down syndrome pregnancies; P = 0.012, 0.001, 0.001, and < 0.001, by Student t test for AFP, hCG, uE3, and inhibin A respectively; † The log 10 means were estimated from the medians; ‡ Values in parentheses were reported by Wald et al (16). AFP, α-fetoprotein; hCG, human chorionic gonadotrophin; uE3, unconjugated Estriol.…”
Section: Figmentioning
confidence: 99%
“…Serum screening has shown to be cost-effective for detecting Down syndrome (23 ) and can reduce the need for invasive amniocentesis (24,25 ). However, recent studies revealed poor accuracy and imprecision of RIA in measuring uE 3 compared with results obtained from liquid chromatographytandem mass spectrometry (LC-MS/MS) analyses, and poor agreement of uE 3 concentrations was observed between RIA and chemiluminescent immunoassay methods (26,27 ). More importantly, discrepancies in assay performance of various kits that cannot be normalized by applying multiples of the median (MoMs) could impact the accuracy of the risk estimation for Down syndrome (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Since 2000, chemiluminescent immunoassays have become commonly used in clinical laboratories in the US for uE 3 testing (26,27 ). This methodology has advantages over other immunoassays in that it is analytically more sensitive and testing can be carried out on an automated analyzer, therefore reducing human error.…”
mentioning
confidence: 99%
“…According to several authors, the effect of analytical variations of β-HCG, AFP and E3 tests on individual risk appears minor; however, some studies report that individual risks are sensitive to minor differences in analytical performances. 7,8 It has been shown that there may be a difference between β-hCG measurements in different analytical systems, especially as different standards are used or the measurement of nicked hCG and other hCG variants in serum affects the measurement. 9 In addition, Serdar et al reported that analytical variations have a great impact on second trimester risk estimation procedures and some articles have reported borderline cases as being problematic.…”
Section: Figurementioning
confidence: 99%